Regimes internacionais e poder informacional: o caso da Netmundial - Rafael Oliveira de Avila (2014)
Contemporary globalization has many aspects, the informational is one of them. This thesis seeks to examine how this informational aspect of contemporary globalization operates under the state and modifies part of its role. For this, it was examined how and through which instruments the state acts. It was identified that the main instrument of the state remains being the power, though, power itself has changed in the context of contemporary globalization. It can also be said that a new power emerged: the informational power. Indeed, it was seen that states use, in addition to their particular power, the international regimes arrangements to act along with their peers and that information also significantly impacts these regimes. Regimes, as noted, are the locus of creation, storage, dissemination and use of information. Finally, the thesis investigates the possibility of existence of a single global regime of information capable of directing the behavior of states today. To this end, we used the case study of the recent event NETmundial, a multistakeholder meeting that discussed the principles of Internet governance. On the one hand, it was concluded that information affects the power and that power, in turn, interferes in international regimes. On the other hand, it was recognized that, although a single global regime of information does not exist, there are many attempts to create international regimes of information policy. Also that the regime about governance over the internet, discussed in NETmundial event, is one example. In this perspective, it was understood that the main question of the thesis how the informational aspect of contemporary globalization affects the role of the state, was answered. The thesis therefore contributes to understanding how the state operates, with their peers, and how the political arrangements made between them are structured, both in light of the influence of the informational dimension; the contemporaneity stigma.